Pemanfaatan Limbah Rumah Tangga untuk Pupuk Organik Cair di Kampung Belentuk Kelurahan Cimahpar - Nurul Husna (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
As many as 70% of the largest contribution of household waste is organic waste. One of the effective handling of organic waste is to process it into organic fertilizer. Organic fertilizers can be in the form of solids or liquids. The abundance of organic waste from household waste can be utilized, one of which is processed into liquid organic fertilizer. Kampung Belentuk has been active in protecting the environment such as making biopori holes and composting. The purpose of the devoted lecturer is to make Belentuk Village residents gain new knowledge in waste management, especially in the manufacture of liquid organicfertilizers. The materials used in making organic liquid fertilizer are vegetable waste, rice washing water, EM4, and sugar. The method used is to cut the remnants of vegetables, put rice water and sugar into a container. EM4 as a source of microorganisms is given as much as 10 cc per 10 liters of water. The solution is then stirred and allowed to stand and the results of the soaking will be seen within 2 weeks.